The Relationship Between Proactive Personality Traits and Professional Values in Final-Year Nursing Students - Dertli, Semiha; Aktura, Seher Cevik (Sakarya Univ, 2024)
Aim: This descriptive, relational study investigated the relationship between final-year nursing students' proactive personality traits and professional values. Method: The research population consisted of 101 final-year nursing students in the nursing department of a university in eastern Turkey between 10-20 December 2022. The study data were collected online using the participant introduction form, the Abbreviated Proactive Personality Scale and the Professional Nursing Values Scale and analyzed using descriptive statistics, independent groups t-test, Kruskal-Wallis and Pearson correlation test. Results: The final-year nursing students were found to have an average of 49.53 +/- 10.34 and 112.34 +/- 15.87 on the Abbreviated Proactive Personality Scale and Professional Nursing Values Scale, respectively, and had a proactive personality and high professional values above the medium level. The study showed that the final-year nursing students who volunteered to become nurses had higher mean scores on the Professional Nursing Values Scale total score and the Professionalism, Activism and Justice subscales, with a statistically significant difference. A moderately significant positive correlation was found between students' Abbreviated Proactive Personality Scale and Professional Nursing Values Scale mean scores (r=0.477, p<0.001). The research found that as students' proactive personality increased, so did their professional values. Conclusion: The study found that students had proactive personalities and high professional values above the moderate level, and as proactive personality traits increased, their professional values also increased. In this regard, developing students' proactive personality traits and professional nursing values may be recommended, as increasing their awareness and conducting research with larger groups.
Keywords: Final year nursing students; Proactive personality; Nursing; Professional nursing values